Context‐dependent behaviour and connectivity of recolonizing brown bear populations identify transboundary conservation challenges in Central Europe. (18th July 2020) - Recio, M. R.; Knauer, F.; Molinari‐Jobin, A.; Huber, Đ.; Filacorda, S.; Jerina, K.
Abstract: Following historical restrictions to isolated and patchy populations, large carnivores like the brown bear Ursus arctos are recolonizing areas of their historical range in Europe. This process is of particular interest in the Alps and the Dinaric Mountains in Central Europe, the largest mountain range in the continent and of transboundary conservation interest. To assist policies focused on the expansion of bears in this region, we conducted habitat selection analyses accounting for different behaviour between three populations (Trentino, pre‐Alps and Dinaric) where bears have adapted to different intensities of human persecution. We then identified the landscape connectivity between these fragmented populations that could provide viable habitat and stepping‐stone patches for recolonization. To handle individual and population differences in space‐use, we modelled habitat selection per population from an individual‐level and integrated results into a multi‐population model using scale‐integrated resource selection functions. We then calculated connectivity indices per patch and the contribution of various countries involved in bear management in the region to enhancing connectivity. Bears mostly selected forests across all populations while preferences for other variables differed among populations and across scales. Bears in the highly humanized habitats of the Trentino selected the most intricate topography, where they could more easily find refuge. Suitable but fragmented habitat patches were common all over the study area with the most suitable habitat in the pre‐Alpine and Dinaric populations. However, the Trentino and pre‐Alp included the patches of maximum/medium priority as stepping‐stones to connect these populations. Transboundary initiatives for the conservation of existing habitat and the facilitation of connectivity are required to promote current bear expansion and reduce conflicts with humans. Our framework provides insight into the adaptive behaviour of large carnivores in human‐dominated landscapes in a conservation context. Abstract : Large carnivores like the brown bear Ursus arctos are recolonizing areas of their historical range in Europe in processes of transboundary conservation interest. We conducted multi‐population and multiscale habitat selection analyses of three populations in the Alps and Dinaric Mountains, where bears have adapted to different intensities of human persecution. We also identified the landscape connectivity between these fragmented populations and the contribution of various countries to enhancing this connectivity. Bears mostly selected forests across all populations and in the highly human‐dominated habitats of the Trentino selected the most intricate topography, ensuring refuge. Suitable but fragmented habitat patches were common all over the study area, and the Trentino and pre‐Alp included the patches of maximum/medium priority as stepping‐stones to connect these populations. Transboundary initiatives for conservation and connectivity are required to promote current bear expansion while reducing conflicts with humans.